2018
DOI: 10.3390/ijerph15040680
|View full text |Cite
|
Sign up to set email alerts
|

The Coaching on Lifestyle (CooL) Intervention for Overweight and Obesity: A Longitudinal Study into Participants’ Lifestyle Changes

Abstract: Combined lifestyle interventions (CLIs) can be effective in reducing weight and improving lifestyle-related behaviours but it is unclear how CLIs can best be implemented in practice in order to achieve sustained lifestyle changes. The Coaching on Lifestyle programme (CooL) is a CLI in the Netherlands, in which professional lifestyle coaches counsel adults and children (and/or their parents) who are obese or at high risk of obesity to achieve a sustained healthier lifestyle. The CooL intervention consists of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 57 publications
4
28
0
1
Order By: Relevance
“…The lack of a control group receiving no intervention does not allow causal conclusions about the effectiveness of CLI and CLI+, but results are in line with observational studies regarding effects on lifestyle and motivation of this specific CLI in primary care ( Rutten et al, 2014 , Helmink et al, 2011 ). Comparable lifestyle interventions have also shown positive results with regard to body composition, although the magnitude of changes differs between studies ( Knowler et al, 2002 , Look Ahead Research Group, 2010 , Tuomilehto et al, 2001 , Goodpaster et al, 2010 , Hardcastle et al, 2008 , Vermunt et al, 2012 , Driehuis et al, 2012 , van Rinsum et al, 2018 ). The decreases in BMI and waist circumference in the current study were markedly larger than found in three earlier studies ( Hardcastle et al, 2008 , Vermunt et al, 2012 , Driehuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of a control group receiving no intervention does not allow causal conclusions about the effectiveness of CLI and CLI+, but results are in line with observational studies regarding effects on lifestyle and motivation of this specific CLI in primary care ( Rutten et al, 2014 , Helmink et al, 2011 ). Comparable lifestyle interventions have also shown positive results with regard to body composition, although the magnitude of changes differs between studies ( Knowler et al, 2002 , Look Ahead Research Group, 2010 , Tuomilehto et al, 2001 , Goodpaster et al, 2010 , Hardcastle et al, 2008 , Vermunt et al, 2012 , Driehuis et al, 2012 , van Rinsum et al, 2018 ). The decreases in BMI and waist circumference in the current study were markedly larger than found in three earlier studies ( Hardcastle et al, 2008 , Vermunt et al, 2012 , Driehuis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions of shorter duration and/or less guidance than e.g. the Look AHEAD trial yielded relevant effects on lifestyle and weight after six to twelve months of guidance ( Goodpaster et al, 2010 , Hardcastle et al, 2008 , van Rinsum et al, 2018 ), while others showed small or even no effects after 2.5 to three years of guidance ( Vermunt et al, 2012 , Driehuis et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 lifestyle coaches, who had completed a post-graduate training course at the Dutch Academy for Lifestyle and Health (AV-LEG), were involved in the pilot programme. More information about the content of the programme can be found elsewhere, as well as the methods, techniques and working approaches used in the intervention [123,162].…”
Section: Cool Interventionmentioning
confidence: 99%
“…The study protocol of the CooL study has been published and presents a detailed description of the study and the methods [123]. The lifestyle changes achieved among CooL participants have been reported in an earlier publication [162]. Briefly, the results showed positive and sustained changes among adults regarding motivation, behaviour-specific cognitions, lifestyle behaviours, quality of life and weight.…”
Section: Cool Studymentioning
confidence: 99%